Erythrosine B Catalyzed Synthesis of trans-Dihydro-4H-furo[3,2-c]chromen-4-ones through Photocatalytic Dehydrogenative sp3 C–O Bond Formation - Das, Sourav; Paul, Suvam; Choudhuri, Tathagata; Sikdar, Papiya; Bagdi, Avik Kumar (Synthesis, 2023)
A simple and efficient visible-light-induced methodology has been developed for the selective synthesis of dihydro-4H-furo[3,2-c]chromen-4-one derivatives via dehydrogenative coupling reaction. The methodology is highly useful for the synthesis of varieties of dihydro-4H-furo[3,2-c]chromen-4-ones from readily accessible reactants under oxygen atmosphere. Importantly, the additive-free approach has been also demonstrated for this transformation. The results of the mechanistic investigation showed that this dehydrogenative reaction proceeded through a radical pathway. Additionally, the synthesized dihydro-4H-furo[3,2-c]chromen-4-one has been transformed into different 4H-furo[3,2-c]chromen-4-ones through simple protocols.
Keywords: photocatalysis; dehydrogenative coupling; erythrosine B; oxygen; dihydro-4H-furo[3,2-c]chromen-4-one